Wir sind Halbierte. Die Entdeckung der DDR in der westdeutschen Literatur vor 1989 - Meier, Albert (Studia Germanica Posnaniensia, 2017)
West German literature has turned its back to the existence of the second German state until the 1980s. Only a few years before the fall of the Berlin wall, three writers started to make the GDR a subject of narration or poetry: Botho Strauß, Peter Schneider and Martin Walser. In different ways, yet unanimously, they complain about the division of Germany dealing with its impact on everyday life and private feelings.